Bilateral activation of STAT3 by phosphorylation at the tyrosine-705 (Y705) and serine-727 (S727) positions and its nuclear translocation in primary sensory neurons following unilateral sciatic nerve injury - Dubový, Petr; Hradilová-Svíženská, Ivana; Klusáková, Ilona; Kokošová, Viktoria; Brázda, Václav; Joukal, Marek (Histochemistry and cell biology, 2018)
Unilateral sciatic nerve compression (SNC) or complete sciatic nerve transection (CSNT), both varying degrees of nerve injury, induced activation of STAT3 bilaterally in the dorsal root ganglia (DRG) neurons of lumbar (L4-L5) as well as cervical (C6-C8) spinal cord segments. STAT3 activation was by phosphorylation at the tyrosine-705 (Y705) and serine-727 (S727) positions and was followed by their nuclear translocation. This is the first evidence of STAT3(S727) activation together with the well-known activation of STAT3(Y705) in primary sensory neurons upon peripheral nerve injury. Bilateral activation of STAT3 in DRG neurons of spinal segments anatomically both associated as well as non-associated with the injured nerve indicates diffusion of STAT3 activation inducers along the spinal cord. Increased levels of IL-6 protein in the CSF following nerve injury as well as activation and nuclear translocation of STAT3 in DRG after intrathecal injection of IL-6 shows that this cytokine, released into the subarachnoid space can penetrate the DRG to activate STAT3. Previous results on increased bilateral IL-6 synthesis and the present manifestation of STAT3 activation in remote DRG following unilateral sciatic nerve injury may reflect a systemic reaction of the DRG neurons to nerve injury.
Keywords: Sensory Receptor Cells; Male; Rats, Wistar; Cell Nucleus; fosfoserin; Sciatic Neuropathy; fosforylace; fosfotyrosin; Systemic reaction; spinální ganglia; Phosphorylation; aktivní transport - buněčné jádro; nervové receptory; Peripheral nerve injury; mužské pohlaví; buněčné jádro; Phosphotyrosine; potkani Wistar; Dorsal root ganglia; nemoci sedacího nervu; krysa rodu Rattus; Animals; Neuroinflammation; Phosphoserine; zvířata; Rats; STAT3 Transcription Factor; transkripční faktor STAT3; Ganglia, Spinal; Active Transport, Cell Nucleus